2019
DOI: 10.12659/msm.915123
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Induced by Oxygen-Glucose Deprivation Mediates the Injury to the Neurovascular Unit

Abstract: Background Autophagy is characterized by the degradation of cellular components in autophagosomes. It plays a significant role in cerebral ischemic injury and has a complex functional connection with apoptosis. The neurovascular unit (NVU) is a structural and functional unit of the nervous system presented as a therapeutic target of stroke. This study aimed to investigate the effect of autophagy induced by ischemic damage on NVUs. Material/Methods SH-SY5Y cells, C6 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…However, two studies showed a reduction of viability (as detected by MTT) starting only at 6 hours of OGD in primary rat brain microvascular ECs [70, 71] and another study using bEnd.3 cells found decreased cell viability (as detected by MTT) and increased annexin A5/PI staining by 6 and 12 hours of OGD [72]. Other studies in primary mouse brain microvascular ECs and bEnd.3 cells detected the start of cell death (according to MTT and active caspase-3) even later, at 12 hours [7375] or 16 hours after OGD onset [76].…”
Section: Systematic Review Of Ec Death In Strokementioning
confidence: 99%
“…However, two studies showed a reduction of viability (as detected by MTT) starting only at 6 hours of OGD in primary rat brain microvascular ECs [70, 71] and another study using bEnd.3 cells found decreased cell viability (as detected by MTT) and increased annexin A5/PI staining by 6 and 12 hours of OGD [72]. Other studies in primary mouse brain microvascular ECs and bEnd.3 cells detected the start of cell death (according to MTT and active caspase-3) even later, at 12 hours [7375] or 16 hours after OGD onset [76].…”
Section: Systematic Review Of Ec Death In Strokementioning
confidence: 99%
“…Ischemia/hypoxia increased the level of microtubule-associated protein 1 light chain 3 (LC3), as was found in undifferentiated (n = 9) (Lai et al 2020 ; Liu et al 2016 , 2021 ; Niu et al 2018 ; Shi et al 2012 ; Wang et al 2017 , 2019c ; Zhi et al 2020 ; Zhou et al 2019 ) and differentiated SH-SY5Y cells (n = 2) (Cheng et al 2019 ; Zhang et al 2019b ). Connexin32 (CX32) was found to inhibit the autophagic effect of nuclear receptor 4A1 (NUR77) during ischemia/hypoxia in one study using undifferentiated SH-SY5Y cells (Ping et al 2021 ).…”
Section: Resultsmentioning
confidence: 79%
“…Ischemic stroke is caused by a sudden interruption of blood flow to the brain, resulting in brain cell death and neurological dysfunction ( 24 ). With increase in the aging population, the number of patients with stroke is also increasing and is predicted to reach 77 million by 2030 ( 25 ).…”
Section: Discussionmentioning
confidence: 99%